HUBUNGAN MINAT DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI DI KELAS XI SMA NEGERI 14 PEKANBARU - Apriani Azmi; Yuslim Fauziah; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This study aims to determine the relationship of interest with student learning outcomes on learning biology class XI SMA Negeri 14 Pekanbaru.Penelitian conducted in January to February 2017. This type of research is a correlation research that aims to see whether there is a relationship between two variables or multiple variables. The subjects of this study were students of class XI IPA 1 academic year 2016/2017 which amounted to 34 students consisting of 22 female students and 12 male students. The sample determination was done by survey method. The research instrument used is a closed questionnaire consisting of 25 statements and 5 indicators of feelings of pleasure, interest, student attention, student involvement and student learning outcomes that comprise aspects of cognitive aspects. The data collected was analyzed using SPSS version 20.00 for windows based on the calculation using Likert scale to know the relationship of interest with learning outcomes. The results showed that the relationship of interest with student learning outcomes on the cognitive aspect to get the value of calculation r of coefficient of product moment correlation is 0.602 which means significant 5% significance level (0.349). Furthermore it can be said that rhitung ≥ rtabel, so the hypothesis accepted and the nature of the relationship of interest with cognitive learning outcomes is positive with strong category.Keywords: Student's Interest And Learning Outcomes, Correlation